Dimeglumin chlorin E6 as a photo-sensitizer in photodynamic therapy in non-oncological diseases - D. Yu. Semenov; V. K. Shubin; E. F. Stranadko; R. N. Komarov; M. V. Ryabov; Yu. K. Bogomazov; V. A. Morokhotov; A. N. Shcherbyuk; S. V. Morozov; Yu. I. Zakharov; E. V. Bondarenko; N. V. Karpov; et al. (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
This review demonstrates the possibilities of photodynamic therapy in treatment of non-tumor pathologies using dimeglumine chlorin E6 as a photosensitizer. Initially, the method was invented for the treatment of cancer and demonstrated its effectiveness and safety. In present photodynamic therapy successfully used in the treatment of the bronchus, skin, stomach, cervix, larynx cancer. In addition to the treatment of different localization tumors, various studies demonstrated other positive effects of photodynamic therapy: antimicrobial, antimycotic, autoimmune, reparative. In the presented review, dimeglumine chlorin E6, which is a derivative of chlorin e6, acts as a photosensitizer. It demonstrates safety, high selectivity of accumulation in tissues, and is characterized by a short period of excretion from the body. Using of dimeglumine chlorin E6 cans significantly reduce the number of side effects associated with long-term skin phototoxicity.